High Prevalence of Developmental Venous Anomaly in Diffuse Intrinsic Pontine Gliomas: A Pediatric Control Study. (16th November 2020) - Roux, Alexandre; Boddaert, Nathalie; Grill, Jacques; Castel, David; Zanello, Marc; Zah-Bi, Gilles; Chrétien, Fabrice; Lefevre, Etienne; Ros, Volodia Dangouloff; Zerah, Michel; Puget, Stéphanie; Pallud, Johan; et al.
Graphical Abstract: